The Role Of The Sukoharjo Regency Transportation Agency in Law Enforcement Against Public Transportation That Does Not Meet Technical And Roadworthiness Requirements - Alisa Wahana Putri; Robby Satri Pamungkas; Shaka Ataullah; Ivena Pasya Jusenda Prasetya; Ira Ramawati; Yokhebed Arumdika (Jurnal Ilmiah Multidisiplin, 2026)
This study examines the law enforcement of public transportation that does not meet technical and roadworthiness requirements in Sukoharjo Regency. This issue is significant because public transportation plays an essential role in public mobility, yet many vehicles still operate without complying with safety and roadworthiness standards. The purpose of this study is to analyze the forms of law enforcement carried out by the Sukoharjo Regency Transportation Agency and to identify factors affecting its effectiveness. The research employs an empirical juridical method by reviewing traffic and road transport regulations and supported by field data. The findings indicate that law enforcement is implemented through supervision and enforcement actions such as vehicle inspections, traffic tickets, and case submissions to the district court. The effectiveness of law enforcement is influenced by legal substance, law enforcement officers, facilities and infrastructure, public legal awareness, and legal culture. This study is expected to contribute both academically and practically to improving traffic safety and public transportation order.